Steering algal metabolic flux via EPS-mediated interfacial buffering for resilient pharmaceutical remediation in microplastic-polluted hotspots - Tengda Ding; Shiqi Lin; Liping Liu; Chunlong Zhang (Bioresource Technology, 2026)

A metabolism-driven multifunctional hydrogel promotes adipocyte differentiation and reduces fibrotic skin repair - Zhangrui Wu; Liping Zhang; Yi Wang; Zixuan Feng; Zeming Zhuang; Xincao Zhong; Chunye Chen; Xiaoying Lin; Yong Wang; Xuewen Wang; Kai Guo; Jun Chen; et al. (Chemical Engineering Journal, 2026)

Enhanced removal of iodine ions using Zn-based metal-organic framework/polypyrrole adsorption membrane - Lingyun Xu; Shanshan Lu; Liping Jiang; Xiaohe Tian; Xijie Lin; Jianhua Qiu (Journal of Environmental Sciences, 2026)

Printable aligned carbon fiber-reinforced polylactic acid composites towards tunable thermal management and mechanical performance - Jiajun Yu; Liping Gong; Purun Wang; Shilong Duan; Qiankun Chen; Shiyu Lin; Zimu Li; Weihua Li; Shuai Liu (Chemical Engineering Journal, 2026)

Microwave-ultrasound enhanced lithium extraction and lithium carbonate preparation from α-spodumene - Enpei Zhu; Shengxuan Zhao; Yijin Guo; Chao Luo; Linqing Dai; Shaohua Yin; Gengwei Zhang; Guo Lin; Libo Zhang; Bingguo Liu; Liping Ding; Yonggang Zuo (Chemical Engineering Journal, 2026)

Immunometabolic regulation and tissue-resident immunity in autoimmune uveitis: from genetic susceptibility to the gut-spleen-eye axis - Liping Lin; Jingqi Zhang; Xuejun Xie (Inflammation Research, 2026)

ROMO1 loss in cholinergic neurons induces mitochondrial ultrastructural damage and ALS-like neuromuscular degeneration - Wei Nie; Zhiwen Jing; Linling Cheng; Lin-Lin Li; Yuxiao Bai; Fengli Xu; Sihan Li; Limei Lin; Xiaohui Dong; Liping Yu; Lei Cai; Bingxing Pan; et al. (Science Bulletin, 2026)

Zn2+-doped Mn-based layered oxide cathode with suppressed P3–O3 phase transition for high-efficiency potassium-ion batteries - Yingna Zhang; Chuye Pan; Zeyu Yuan; Liping Duan; Haowei Tang; Jiaying Liao; Yue Lin; Xiaosi Zhou (Science Bulletin, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

LncRNA DLX6-AS1 Regulates the Pathological Process Related to Alzheimer’s Disease via miR-204-5p - Minggang Jiang; Yang Lin; Liping Wang; Kaiyun Ou (NeuroMolecular Medicine, 2026)

Rational design of antibacterial and biodegradable PCL/oxidized cassava starch/Nisin ternary films based on molecular docking - Xiangrui Ren; Li Niu; Liping Zhao; Wenqing Zhao; Qian Lin; Shuangfeng Guo; Yayun Hu; Wenhao Li (Journal of Food Engineering, 2026)

Facile fabrication of PTFE/PET composite membrane with reinforced hydrophilic and antifouling properties for sustainable decentralized water system purification - Ludi Song; Yujie Fang; Xin Chen; Ziyuan Zhou; Liping Chen; Jun Yang; Ying Li; Yaqin Wu; Haitao Zhu; Lin Zhang; Congjie Gao (Journal of Environmental Management, 2026)

Magnolol disrupts membrane integrity and enhances colistin activity via a NagR-Mediated susceptibility in foodborne Aeromonas hydrophila - Xin Chen; Jinpeng Shi; Siyan Chen; Linbin Chen; Shuaiyuan Tang; Ruixiang Shi; Zhihan Yu; Wenbo Yu; Tianlong Lai; Yibin Liao; Liping Li; Xiangmin Lin (Food Bioscience, 2026)

High-Efficiency N-acetylneuraminic acid biosynthesis in plasmid-free Escherichia coli MG1655 - Qian Lin; Yuanlin Liu; Wenbo Zhang; Liping Qiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

The empowerment path of corporate carbon performance by executive environmental background - Liping Wang; Shanyu Lin; Qianwen Ma; Chuang Li (Environment, Development and Sustainability, 2026)

Polyvinyl chloride microplastics exposure accelerates endometrial cancer progression via regulating AHR/CYP1A1 signaling pathway - Liping Zhang; Dezhao Chen; Rencai Fan; Lijin Chen; Hao Chen; Meiting Wu; Jialin Liu; Xiaoyan Lin (Toxicology, 2026)

Mechanical behavior and design of an eight-bolt extended stiffened end-plate connection with oversized holes: Experimental and numerical studies - Bin Jiang; Liping Duan; Siwei Lin; Jiming Liu; Ge Qu; Jincheng Zhao (Engineering Structures, 2026)

MRI image segmentation of the major lower leg muscles using deep learning: application in biomechanical analysis - Yongsheng Lin; Zhongzheng Wang; Zhicheng Zheng; Antea Destro; Haoxin Chen; Liping Zhu; Yongjin Zhou; Ruoli Wang (Medical & Biological Engineering & Computing, 2026)

Three new terpenes with potential antibacterial and anti-COVID-19 activities from the stems of Eurya chinensis R. Br - Chen Liping; Lin Shaodan; Pan Yongchen; Huijun Liang; Chen Jiayan; Xin Lian; Li Guangying; Xiong Xiubi; Jie Yuan; Jiewei Wu (Natural Product Research, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

SERS fingerprinting of β2-agonists for anti-doping based on Au–COF substrate - Siqing Liu; Liping Chen; Xingju Li; Ruxi Lin; Yunxin Zhang; Xiaojun Luo (Analytica Chimica Acta, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Oral cerium-based nanoplatform conjugated with gold to load anti-miR-301a for pH-transited multi-modal therapy of inflammatory bowel disease - Jiafeng Zou; Qingdong Ji; Xier Pan; Yiting Lin; Xinlin Zhao; Xinyi Chen; Liping Yang; Jing Lu; Shuhui Zheng; Zhuo Zhang; Kun Jiang; Feng Gao (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

Unveiling decrosslinking degree on polyamide nanofiltration membranes: Structure–performance relationship and micropollutant removal - Xiaozhen Lu; Lin Wang; Xuewu Zhu; Liping Qiu; Zhe Yang; Daliang Xu; Jiashuai Wei; Qianxin Zhang; Chunzhao Chen; Shan Niu; Bin Liu (Water Research, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Metal(loid) accumulation and foliar physiological responses in Oryza sativa L. induced by PM1 exposure from various emission sources - Meixuan Fang; Yue Yang; Baofeng Zhang; Yingluo Chen; Jingdong Mao; Liping Lou; Qi Lin (Journal of Environmental Sciences, 2026)

Metformin Ameliorates Early Brain Injury After Subarachnoid Hemorrhage Via Improving Endoplasmic Reticulum Stress and Mitochondrial Stress-Mediated Ca2+ Imbalance - Zhonghua Zhang; Jingbei Zhang; Liping Li; Lin Zong (Molecular Neurobiology, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

Mechanism of piezoelectric field-enhanced electron transfer during peroxymonosulfate activation with MoS2/PVDF-HFP films - Tingting Cao; Liping Lin; Yanan Li; Wangshu Tong (Journal of Environmental Chemical Engineering, 2025)

Characterization of flavor profile and microbial community dynamics in naturally fermented sour watermelon - Lin Zhang; Dengcheng Li; Lijuan Zhou; Liping Zhu; Ruiqi Zhang; Qiongping Hong; Sixin Liu; Congfa Li (Food Research International, 2025)

Triple-pronged strategy: A theranostic hydrogel platform with near-infrared chemiluminescence imaging-guided sonodynamic therapy for bacterial-infected wound healing - Jiaxin Yang; Kaijia Lin; Ke Xu; Liping Zhang; Qian Zhang; Gelin Xu; Yachao Wang; Haixing Feng; Yayun Xu; Yanqin Fan; Ziwei Wang; Zihan Wu; et al. (Chemical Engineering Journal, 2025)

Integrating geological indicators for enhanced mapping of soil organic matter in hilly landscapes - Shuangshuang Shao; Liping Li; Lin Yang; Baowei Su; Huan Zhang; Chao Gao; Likun Gu; Yalu Zhang; Weiqin Xing; Mingyu Yu (Journal of Cleaner Production, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

Recent advances in China’s planetary science research - Yongxin Pan; Wei Lin; Liping Qin (Science China Earth Sciences, 2025)

Different Detection Strategies of Pediocin-Like Produced by Pediococcus pentosaceus - Hongbiao Li; Huojian Zheng; Lanxin Li; Yi Lin; Qiuxiang Cheng; Liping Wang; Yueliang Zhao; Zhenmin Liu (Probiotics and Antimicrobial Proteins, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Comparative genome and transcriptome analysis reveals pathogenic mechanisms of Neoscytalidium dimidiatum in pitaya - Shanyu Lin; Jinling Huang; Jianjun Jiang; Junjie Li; Liping Qin; Xiuhong Lu (Physiological and Molecular Plant Pathology, 2025)

Water flow-driven high piezo-photocatalytic efficacy in superthin and densely porous GO-TiO2/PVDF-HFP composite film for ROS generation - Jialin Zhuang; Yechen Wang; Liping Lin; Jiaying Xiao; Jiahui Cai; Yingmo Hu; Qi An (Chemical Engineering Journal, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Decoupling Pharmaceutical Contamination and Antibiotic Resistance Risks in Mid-Yangtze Drinking Water Systems: The Pivotal Role of Nutrient-Driven Horizontal Gene Transfer - Peng He; Jingqian Peng; Lin Wei; Yuting Wu; Liping Zhang; Qiaohong Zhou; Shaoxian Song; Mildred Quintana; Zhenbin Wu; Junmei Wu (Environmental Management, 2025)

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Flexible and cleaner alkaloid extraction of Sophora Flavescens and Heterosmilax Japonica with the aid of process analytical technology - Liping Liu; Lin Miao; Wenlong Li; Tongchuan Suo (Sustainable Chemistry and Pharmacy, 2025)

Comparative assessment of silver nanoparticle and silver nitrate toxicities in Mytilus galloprovincialis - Zimin Cai; Zihan Xing; Mingzhe Xu; Yuting Zhao; Lin Ye; Wei Sun; Ruijia Tao; Liuya Mi; Bowen Yang; Lei Wang; Yancui Zhao; Xiaoli Liu; et al. (Marine Environmental Research, 2025)

Enhancing soil carbon sequestration in jasmine gardens: Differential effects of straw and biochar on mineral-associated and particulate organic carbon - Xiaoying Ren; Wenwen Yang; Liping Ye; Siyan Lin; Yuan Li; Weiqi Wang; Jordi Sardans; Junma Chen; Shiyu Chen; Siqi Yu; Li Hou; Akash Tariq; et al. (Journal of Environmental Management, 2025)

Lignin-enhanced fungal-bacterial consortium for degradation of petroleum hydrocarbon contaminants - Lin Wu; Jiajie Wang; Tao Jin; Xiangyuan Zhou; Liping Wang (Journal of Environmental Management, 2025)

Aminoguanidinium-engineered crater morphology in nanofiltration membranes: Unraveling transport mechanisms and structure-dependent purification performance - Xiaozhen Lu; Lin Wang; Xuewu Zhu; Liping Qiu; Heng Liang; Haiqing Chang; Daliang Xu; Xiaobin Tang; Jiashuai Wei; Bin Liu (Chemical Engineering Journal, 2025)

Copper doped carbon dots for selective determination of regulated aniline additives and safe hair dyeing - Zhanghong Guo; Lin Zhou; Liping Zhang; Haining Cui; Jinxin Ma; Chan Wang; Qijun Song (Analytica Chimica Acta, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Ecotoxicological effects of the neonicotinoid insecticide dinotefuran on springtails (Folsomia candida) at soil residual concentration - Jiale Zhang; Herui Zhang; Caihong Yu; Ronghua Lin; Yanhua Hou; Min Li; Huixin Liang; Liping Chen; Xinyue Gao; Siqi Chen (Pesticide Biochemistry and Physiology, 2025)

Mechanical performance and design method of a stiffened T-stub with four-row bolts and oversized holes - Bin Jiang; Liping Duan; Siwei Lin; Yan Zhu; Jiming Liu; Jincheng Zhao (Engineering Structures, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Impact of organic acids on aroma release in light-flavor Baijiu: A focus on key aroma-active compounds - Lin Yuan; Yunjie Li; Liuyan Zheng; Yifan Qin; Xin Zhang; Lijuan Ma; Huan Zhang; Liping Du (Food Bioscience, 2025)

Long-term effectiveness of heavy metal(loid) stabilization: Development of an assessing method - Yanqing Liu; Zewen Wang; Xiao Tan; Deyi Hou; Liping Fang; Aijun Lin; Fangbai Li; Guilan Duan (Environmental Pollution, 2025)

Remediation of various phenanthrene-contaminated soils using persulfate-Pseudomonas aeruginosa GZ7: Soil properties, radical formation, and microbial community - Na Liu; Xiangyuan Zhou; Lin Wu; Tao Jin; Kang Li; Liping Wang (Journal of Environmental Chemical Engineering, 2025)

Memory Reconsolidation Updating in Substance Addiction: Applications, Mechanisms, and Future Prospects for Clinical Therapeutics - Shihao Huang; Xiaoxing Liu; Zhonghao Li; Yue Si; Liping Yang; Jiahui Deng; Yixiao Luo; Yan-Xue Xue; Lin Lu (Neuroscience Bulletin, 2025)

Inhibitory effect and mechanism of violacein on planktonic growth, spore germination, biofilm formation and toxin production of Bacillus cereus and its application in grass carp preservation - Xiangdi Lou; Qiang Zhou; Qiyue Jiang; Liping Lin; Wenwu Zhu; Xiaoyu Mei; Jianhua Xiong; Yanyan Gao (International Journal of Food Microbiology, 2025)

DNA-labeled chitosan nanoparticles: A potential new surrogate for assessing rotavirus attenuation and transport in sand filtration water treatment - Liping Pang; Travis Issler; Beth Robson; Richard Sutton; Susan Lin; Jill Allmendinger; Sujani Ariyadasa; Aruni Premaratne; Craig Billington; Elmar J. Prenner (Environmental Research, 2025)

Molecular insights into the anti-spoilage effect of salicylic acid in Favorita potato processing - Wenhua Wang; Liping Hong; Zhijun Shen; Mingqiong Zheng; Hongyan Meng; Ting Ye; Zhikai Lin; Lianghua Chen; Ying Guo; Enming He (Food Chemistry, 2024)

Estimating potato aboveground biomass using unmanned aerial vehicle RGB imagery and analyzing its relationship with tuber biomass - Yanran Ye; Liping Jin; Chunsong Bian; Guolan Xian; Yongxin Lin; Jiangang Liu; Huachun Guo (Field Crops Research, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

The long-term effects of norgestrel on the reproductive and thyroid systems in adult zebrafish at environmentally relevant concentrations - Shuyan Mai; Yan-Qiu Liang; Shuhui Zhou; Hongjie Lin; Zhongdian Dong; Chang-Gui Pan; Qingwei Kong; Shaoshuai Wang; Shiqing Wang; Zhong Lin; Liping Hou (Aquatic Toxicology, 2024)

Exploring the short-term effects of extreme temperatures on tuberculosis incidence in Shantou, China: a Coastal City perspective - Yaqian Su; Ruiming Chen; Zhuanghao Chen; Jianxiong Lin; Hui Fu; Zicheng Cao; Qiaocheng Chang; Liping Li; Suyang Liu (International Archives of Occupational and Environmental Health, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

The impact of co-exposure to polystyrene microplastics and norethindrone on gill histology, antioxidant capacity, reproductive system, and gut microbiota in zebrafish (Danio rerio) - Shuhui Zhou; Hongjie Lin; Ziyun Liu; Xiaoyi Lian; Chang-Gui Pan; Zhongdian Dong; Zhong Lin; Chengyong Li; Liping Hou; Yan-Qiu Liang (Aquatic Toxicology, 2024)

Remediation of phenanthrene contaminated soil by persulphate coupled with Pseudomonas aeruginosa GZ7 based on oxidation prediction model - Zhenxian Yao; Xiangyuan Zhou; Tao Jin; Liping Wang; Na Liu; Lin Wu (Environmental Science and Pollution Research, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Combinatorial preparation and structural characterization of anthocyanins and aglycones from Purple-heart Radish for evaluation of physicochemical stability and pancreatic lipase inhibitory activity - Tiefeng Yuan; Liping Wang; Linzhou Chen; Jinjian Zhong; Yuyang Lin; Yihan Wang; Chen Lin; Huajun Fan (Food Chemistry, 2024)

Cyclodextrin-based ternary supramolecular deep eutectic solvents for efficient extraction and analysis of trace quinolones and sulfonamides in wastewater by adjusting pH - Jingyu Zhang; Shang Li; Liping Yao; Yulin Han; Kexian Chen; Mingrong Qian; Zuguang Li; Hui Lin (Analytica Chimica Acta, 2024)

Hierarchical structural modulation and Co-Construction of selenium vacancy in ZnSe/NiSe2 heterojunctions to enhance cycling stability and fast ion diffusion kinetics for lithium-ion and sodium-ion batteries - Peng Zhou; Liping Wang; Mingyu Zhang; Qizhong Huang; Zhean Su; Xiaodong Wang; Dingrong Guo; Mingdong Liao; Ping Xu; Xiangbao Lin (Chemical Engineering Journal, 2024)

Deciphering the Epigenetic Landscape: Placental Development and Its Role in Pregnancy Outcomes - Yujia Chen; Zhoujie Ye; Meijia Lin; Liping Zhu; Liangpu Xu; Xinrui Wang (Stem Cell Reviews and Reports, 2024)

Short-term effects of substrate surface structure on macroinvertebrates community structure and functional characteristics - Yufu Gao; Liping Rong; Xiangyu Zhao; Xinyue Wang; Chenlu Lin; Lina Cao; Haijun Yang (Ecological Engineering, 2024)

Advances in synthesis and application of amphoteric polymer-based water treatment agents - Wei Yu; Liping Xiong; Jiaheng Teng; Cheng Chen; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Desalination, 2024)

Different biological responses of Skeletonema costatum and Prorocentrum donghaiense to polymetallic nodules from seawaters - Shuangshuang Lin; Jiandi Li; Liping Jia; Xuguang Huang; Lei Wang (Aquatic Toxicology, 2024)

LncRNA-AC020978 Promotes Metabolic Reprogramming in M1 Microglial Cells in Postoperative Cognitive Disorder via PKM2 - Genghuan Wang; Jian Shen; Qiaobing Guan; Yingcong Lin; Liping Zhai; Heping Shen (Molecular Neurobiology, 2024)

Oil mistparticulate matter exposure induces hyperlipidemia-related inflammation via microbiota/ SCFAs/GPR43 axis inhibition and TLR4/NF-κB activation - Huanliang Liu; Huipeng Nie; Yue Shi; Wenqing Lai; Liping Bian; Lei Tian; Kang Li; Zhuge Xi; Bencheng Lin (Environmental Pollution, 2024)

Acoustoelectric materials & devices in biomedicine - Xinyue Zhang; Yihe Zhang; Jiahe Zhang; Jing Shang; Liping Lin; Qi Liu; Qi An (Chemical Engineering Journal, 2024)

p-Toluenesulfonic acid enhanced neutral deep eutectic solvent pretreatment of soybean straw for efficient lignin removal and enzymatic hydrolysis - Wenxuan Wu; Peiwen Zhu; Liping Luo; Hongyan Lin; Yuheng Tao; Lingyu Ruan; Liqun Wang; Qing Qing (Bioresource Technology, 2024)

Short-term exposure to ozone may trigger the onset of Kawasaki disease: An individual-level, case-crossover study in East China - Yixiang Zhu; Renjie Chen; Cong Liu; Yue Niu; Xia Meng; Su Shi; Kexin Yu; Guoying Huang; Liping Xie; Siyuan Lin; Min Huang; Meirong Huang; et al. (Chemosphere, 2024)

An angle correction method based on the influence of angle and travel speed on deposition in the air-assisted spray - Jinlong Lin; Jinping Cai; Liping Xiao; Kuan Liu; Jian Chen; Jing Ma; Baijing Qiu (Crop Protection, 2024)

Electric field as extracellular enzyme activator promotes conversion of lignocellulose to humic acid in composting process - Lu Zhang; Xuan Wang; Hongge Wang; Yubo Cao; Liping Weng; Lin Ma (Bioresource Technology, 2024)

Study of the impact of digitization on the carbon emission intensity of agricultural production in China - Liping Zhao; Xi Rao; Qiaowen Lin (Science of The Total Environment, 2023)

Insight into the impacts of pyrolysis time on adsorption behavior of Pb2+ and Cd2+ by Mg modified biochar: Performance and modification mechanism - Conghui Zhang; Dongsheng Yang; Wei Liu; Yingbo Dong; Liping Zhang; Hai Lin (Environmental Research, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Long-term ozone exposure is negatively associated with estimated glomerular filtration rate in Chinese middle-aged and elderly adults - Yiqin Zhang; Chen Tang; Yuwen Liu; Hanxiang Jiang; Jiaosheng Lu; Zhonghua Lu; Liping Xu; Siyu Zhang; Lina Zhou; Jing Ye; Xianfa Xuan; Ting Wu; et al. (Chemosphere, 2023)

Study on the influence pattern and efficiency enhanced mechanism of acoustic–chemical spray dust reduction - Bo Zhao; Peng Xiao; Shugang Li; Xiaoxiao Liu; Haifei Lin; Dongjie Yan; Zixi Chen; Liping Chen (Science of The Total Environment, 2023)

Single-cell dynamics of liver development in postnatal pigs - Lin Rao; Liping Cai; Lusheng Huang (Science Bulletin, 2023)

All-in-one self-floating porous foams as robust heat-blocking layers for efficient photothermal conversion and solar desalination - Liping Ren; Wei Zhou; Lei Wang; Kuo Lin; Yachao Xu; Jiaxing Wu; Ying Xie; Honggang Fu (Science Bulletin, 2023)

Circumstellar material ejected violently by a massive star immediately before its death - Jujia Zhang; Han Lin; Xiaofeng Wang; Zeyi Zhao; Liping Li; Jialian Liu; Shengyu Yan; Danfeng Xiang; Huijuan Wang; Jinming Bai (Science Bulletin, 2023)

Whole-genome sequencing and bacteriocin purification of Lactiplantibacillus plantarum HY41 conﬁrms bactericidal and probiotic potential - Hongbiao Li; Ting Liu; Xiuqin Zhang; Zhiguo Xiong; Qing Hong; Shuang Jia; Yi Lin; Liping Wang; Yueliang Zhao (International Biodeterioration & Biodegradation, 2023)

Tulsi (Ocimum sanctum) mediated Co nanoparticles with their anti-inflammatory, anti-cancer, and methyl orange dye adsorption properties - Han Jiang; Selvam Sathiyavimal; Liping Cai; Sandhanasamy Devanesan; Shaban R.M. Sayed; G.K. Jhanani; Junqing Lin (Environmental Research, 2023)

Developmental dynamics of the single nucleus regulatory landscape of pig hippocampus - Siyu Yang; Dong Chen; Lei Xie; Xiaoxiao Zou; Yanyuan Xiao; Lin Rao; Tianxiong Yao; Qing Zhang; Liping Cai; Fei Huang; Bin Yang; Lusheng Huang (Science China Life Sciences, 2023)

Enhanced simultaneous removal of sulfamethoxazole and zinc (II) in the biochar-immobilized bioreactor: Performance, microbial structures and gene functions - Xi Chen; Hai Lin; Yingbo Dong; Bing Li; Chenjing Liu; Liping Zhang; Yanrong Lu; Qi Jin (Chemosphere, 2023)

Cyberinformatics tool for in-season crop-specific land cover monitoring: Design, implementation, and applications of iCrop - Chen Zhang; Liping Di; Li Lin; Haoteng Zhao; Hui Li; Anna Yang; Liying Guo; Zhengwei Yang (Computers and Electronics in Agriculture, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

A cleaner and sustainable method for recovering rare earth and cobalt from NdFeB leaching residues - Liping Zhang; Wanhai Xiao; Guobiao Li; Dong Wang; Jian Wu; Haojie Du; Yong Lin; Chunlin Ye; Tao Qi; Zhi Wang (Journal of Cleaner Production, 2023)

Heterogeneous activation of permonosulfate by biochar supporting CuCoFe layered double hydroxide for rapid degradation of phenanthrene - Lin Wu; Tao Jin; Dan Li; Liping Wang; Yichen Sun (Journal of Environmental Chemical Engineering, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

Comparative reductions of norovirus, echovirus, adenovirus, Campylobacter jejuni and process indicator organisms during water filtration in alluvial sand - Louise Weaver; Phillip Abraham; Liping Pang; Naveena Karki; Erin McGill; Susan Lin; Judith Webber; Laura Banasiak; Murray Close (Science of The Total Environment, 2023)

A series of bifunctional ReBaCo2O5+ perovskite catalysts towards intermediate-temperature oxygen reduction reaction and oxygen evolution reaction - Lin Li; Ziwei Dong; Tian Xia; Xiang Li; Qiang Li; Liping Sun; Hui Zhao; Lihua Huo (Chemical Engineering Journal, 2023)

The efficiency of full-scale subsurface constructed wetlands with high hydraulic loading rates in removing pharmaceutical and personal care products from secondary effluent - Jiaxi Wang; Xia Yu; Hui Lin; Jiusi Wang; Liping Chen; Yanzhou Ding; Shuai Feng; Jingjing Zhang; Beibei Ye; Xiping Kan; Qian Sui (Journal of Hazardous Materials, 2023)

Efficient hexavalent chromium removal by nano-cerium oxide functionalized biochar: Insight into the role of reduction - Kun Luo; Nengfa Lin; Xue Li; Ya Pang; Liping Wang; Min Lei; Qi Yang (Journal of Environmental Chemical Engineering, 2023)

Unique porous ZnS-CdS-CoSx Reuleaux triangle nanosheets: Highly promoted visible-light photocatalytic H2 evolution via synergistic effect of Z-scheme heterojunction and vacancy defects - Liping Wang; Yanyan Li; Hanchu Chen; Ying Zuo; Hui Wang; Jixiang Xu; Haijiao Xie; Haifeng Lin; Lei Wang (Fuel, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Unraveling the highly efficient synergy of adsorption and degradation for norfloxacin elimination by Mo/Fe anchored carbon fiber aerogel via peroxydisulfate activation - Wei Liu; Yingbo Dong; Dongsheng Yang; Conghui Zhang; Liping Zhang; Yanrong Lu; Qi Jin; Zhirui Liu; Junfei Liu; Hai Lin (Chemical Engineering Journal, 2023)

Longitudinal plasma magnesium status during pregnancy and the risk of gestational diabetes mellitus: a prospective cohort study - Xiyu Cao; Meng Wu; Guofu Zhang; Lixia Lin; Menghan Tu; Daxiang Xiao; Chunrong Zhong; Huaqi Zhang; Siyu Yang; Jin Liu; Xu Zhang; Xi Chen; et al. (Environmental Science and Pollution Research, 2023)

Selective removal behavior of lead and cadmium from calcium-rich solution by MgO loaded soybean straw biochars and mechanism analysis - Hai Lin; Dongsheng Yang; Conghui Zhang; Wei Liu; Liping Zhang; Yingbo Dong (Chemosphere, 2023)

Zirconium tungstate reinforced energetic composites with inhibited thermal expansion and reduced thermal stress - Congmei Lin; Liangfei Bai; Liyuan Wei; Ruqin Liu; Shiliang Huang; Cui Zhang; Xiaoqing Tu; Zhijian Yang; Feiyan Gong; Chengcheng Zeng; Ling Ding; Liping Pan; et al. (Chemical Engineering Journal, 2023)

Performance of Sludge in the UASB Reactor for Treating Sulfate Wastewater: Sulfate Removal and Changes in the Community Structure Before and After Reaction - Liping Niu; Shuang Sun; Fangying Yu; Xinyue Zhang; Shiying Fan; Yue Sun; Wenlong Lin; Bowen Wang; Xingde Zhang (Water, Air, & Soil Pollution, 2023)

Exploring key physicochemical sediment properties influencing bioleaching of heavy metals - Chuncheng Wu; Xinyi Hu; Haizhen Wang; Qi Lin; Chaofeng Shen; Liping Lou (Journal of Hazardous Materials, 2023)

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

100% N2O inhibition in photocatalytic NOx reduction by carbon particles over Bi2WO6/TiO2 Z-scheme heterojunctions - Ruting Yuan; Mingtao Wang; Lijun Liao; Wei Hu; Ziyu Liu; Zhaohui Liu; Liping Guo; Ke Li; Yuezhi Cui; Feng Lin; Furong Tao; Wei Zhou (Chemical Engineering Journal, 2023)

Effects of acid/alkali-pretreated peanut shells as a cheap carbon source for the bio-reduction of sulfate - Hai Lin; Tianyu Zhi; Liping Zhang; Chenjing Liu; Yingbo Dong (Journal of Cleaner Production, 2023)

Oxidative stress and immune response of hepatopancreas in Chinese mitten crab Eriocheir sinensis under lipopolysaccharide challenge - Lin Zhou; Lanlu Chu; Jinliang Du; Zhijuan Nie; Liping Cao; Jiancao Gao; Gangchun Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

An ultra-sensitive and specific nanoplasmonic-enhanced isothermal amplification platform for the ultrafast point-of-care testing of SARS-CoV-2 - Juxiang Liu; Ping Chen; Xulong Hu; Liping Huang; Zhi Geng; Hao Xu; Wenjun Hu; Lin Wang; Ping Wu; Gang L. Liu (Chemical Engineering Journal, 2023)

Halloysite nanotube confined interface engineering enhanced catalytic oxidation of photo-Fenton reaction for aniline aerofloat degradation: Defective heterojunction for electron transfer regulation - Wei Liu; Yingbo Dong; Junfei Liu; Liping Zhang; Yanrong Lu; Hai Lin (Chemical Engineering Journal, 2023)

Bistable electrochromic dual-output array display based on intramolecular proton coupled electron transfer - Chengcheng Wang; Jiashuang Li; Wenhua Lin; Jingwen Wang; Yuhua Chen; Bingzhen Li; Liping Zhang; Shaohai Fu (Chemical Engineering Journal, 2023)

RNAseq-based transcriptome analysis of lettuce infected by the necrotrophic fungus Sclerotinia Sclerotiorum - Liguang Tang; Bincai Wang; Liping Song; Chuying Yu; Chufa Lin; Changbin Gao; Daohong Jiang; Aihua Wang (European Journal of Plant Pathology, 2023)

Insm1 promotes differentiation of retinal progenitor cells toward photoreceptor cells in the developing retina through up-regulation of SHH - Pengyi Zhou; Youmei Xu; Lin Yang; Pan Meng; Ju Guo; Zhenhui Liu; Bo Jin; Kunpeng Xie; Haiyan Zhu; Liping Du; Xuemin Jin (Journal of Molecular Histology, 2022)

Promoting effect of Fe/La loading on γ-Al2O3 catalyst for hydrolysis of carbonyl sulfur - Panting Gao; Yuran Li; Yuting Lin; Liping Chang; Tingyu Zhu (Environmental Science and Pollution Research, 2022)

Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Feng Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Correction: Co-axial Projective Imaging for Augmented Reality Telementoring in Skin Cancer Surgery - Fan Zhang; Carlo M. Contreras; Pengfei Shao; Liping Zhao; Bingxuan Wu; Chenmeng Li; Tao Lin; Xiaohong Zhong; Zhongliang Lang; Peng Liu; Ronald X. Xu (Annals of Biomedical Engineering, 2022)

Quantitative synthetic MRI reveals grey matter abnormalities in children with drug-naïve attention-deficit/hyperactivity disorder - Shu Su; Yingqian Chen; Yan Dai; Liping Lin; Long Qian; Qin Zhou; Mengsha Zou; Hongyu Zhang; Meina Liu; Xianhong Xiang; Zhiyun Yang (Brain Imaging and Behavior, 2022)

Pharmaceuticals in drinking water sources and tap water in a city in the middle reaches of the Yangtze River: occurrence, spatiotemporal distribution, and risk assessment - Peng He; Junmei Wu; Jingqian Peng; Lin Wei; Liping Zhang; Qiaohong Zhou; Zhenbin Wu (Environmental Science and Pollution Research, 2022)

Complete nucleotide sequence of a novel partitivirus from Brassica campestris L. ssp. chinensis - Liguang Tang; Liping Song; Chufa Lin; Bincai Wang; Jiazao Lin; Changbin Gao; Aihua Wang (Archives of Virology, 2021)

A novel negative-stranded RNA virus of the order Bunyavirales identified in Brassica campestris L. ssp. chinensis - Liguang Tang; Liping Song; Zhibiao Ye; Chufa Lin; Bincai Wang; Jiazao Lin; Changbin Gao; Aihua Wang (Archives of Virology, 2021)

Positive virus detection in patients who recovered from COVID-19 during quarantine period between discharge and home: a two-center experience in Wuhan, China - Xiaobing Wang; Ping Zhang; Jun Xiao; Yue Zhu; Lin Zhang; Liping Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Spatial distribution of n-alkanes in surface sediments of Selin Co Lake, central Tibetan Plateau, China - Qiangqiang Kou; Xiao Lin; Junbo Wang; Siwei Yu; Jinlei Kai; Andreas Laug; Liping Zhu (Journal of Paleolimnology, 2021)

Over expression of a Chitinase 2 gene from Chinese Wild Strawberry improves resistance to anthracnose disease in transgenic Arabidopsis thaliana - Zhifeng Wen; Jinhui Bai; Lin Wang; Liping Yao; Bilal Ahmad; Muhammad Hanif; Qingxi Chen (Plant Biotechnology Reports, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Development of in-situ Micro-Raman spectroscopy system for autoclave experimental apparatus - Lin Chen; Heping Li; Shengbin Li; Liping Xu; Sen Lin; Hongbin Zhou (Acta Geochimica, 2020)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Drug vector representation: a tool for drug similarity analysis - Liping Lin; Luoyao Wan; Huaqin He; Wei Liu (Molecular Genetics and Genomics, 2020)

Simulation and construction of the glacier mass balance in the Manas River Basin, Tianshan, China from 2000 to 2016 - Guining Zhao; Zhengyong Zhang; Lin Liu; Zhongqin Li; Puyu Wang; Liping Xu (Journal of Geographical Sciences, 2020)

Topological Shape Changes Weaken the Innate Defensive Response to Visual Threat in Mice - Yan Huang; Lei Li; Kun Dong; Hongsi Tang; Qingning Yang; Xianglian Jia; Yundan Liao; Wenbo Wang; Zhen Ren; Lin Chen; Liping Wang (Neuroscience Bulletin, 2020)

Leaf spot of Polygonatum odoratum caused by Colletotrichum spaethianum - Liping Liu; Lin Zhang; Penglei Qiu; Yu Wang; Yanni Liu; Yu Li; Jie Gao; Tom Hsiang (Journal of General Plant Pathology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

Comparative transcript profiling and cytological observation of the newly bred recessive genic male sterility non-heading Chinese cabbage (Brassica rapa ssp. chinensis) line WS24-3A - Liping Song; Xia Li; Feng Zu; Changbin Gao; Bincai Wang; Chufa Lin; Jinxing Tu; Aihua Wang; Guolin Zhou (Genes & Genomics, 2019)

Model test for water inrush caused by karst caves filled with confined water in tunnels - Weimin Yang; Xin Yang; Zhongdong Fang; Shaoshuai Shi; Hao Wang; Lin Bu; Liping Li; Zongqing Zhou (Arabian Journal of Geosciences, 2019)

Association of Body Mass Index and Risk of Stroke After Acute Minor Stroke or TIA: a Post Hoc Analysis of a Randomized Controlled Trial - Weiqi Chen; Yuesong Pan; Jing Jing; Xingquan Zhao; Liping Liu; Xia Meng; Yilong Wang; Yi Lin; Yongjun Wang (Neurotoxicity Research, 2019)

The Glutamatergic Postrhinal Cortex–Ventrolateral Orbitofrontal Cortex Pathway Regulates Spatial Memory Retrieval - Xinyang Qi; Zhanhong Jeff Du; Lin Zhu; Xuemei Liu; Hua Xu; Zheng Zhou; Cheng Zhong; Shijiang Li; Liping Wang; Zhijun Zhang (Neuroscience Bulletin, 2019)

Influences of Appalachian orography on heavy rainfall and rainfall variability associated with the passage of hurricane Isabel by ensemble simulations - Guy Oldaker; Liping Liu; Yuh-Lang Lin (Meteorology and Atmospheric Physics, 2019)

Numerical Investigation to Influence of Perforation Angle on Hydraulic Fracturing Process - Lin Bu; Shucai Li; Shaoshuai Shi; Xiaokun Xie; Liping Li; Zongqing Zhou (Geotechnical and Geological Engineering, 2019)

Gene co-expression network analysis identifies trait-related modules in Arabidopsis thaliana - Wei Liu; Liping Lin; Zhiyuan Zhang; Siqi Liu; Kuan Gao; Yanbin Lv; Huan Tao; Huaqin He (Planta, 2019)

A thiopyran derivative with low murine toxicity with therapeutic potential on lung cancer acting through a NF-κB mediated apoptosis-to-pyroptosis switch - Liping Chen; Bixia Weng; Huimin Li; Haonan Wang; Qian Li; Xiaoyan Wei; Hui Deng; Sicen Wang; Chengxi Jiang; Renyu Lin; Jianzhang Wu (Apoptosis, 2019)

Reciprocal Regulation of OmpR and Hfq and Their Regulatory Actions on the Vi Polysaccharide Capsular Antigen in Salmonella enterica Serovar Typhi - Ying Zhang; Lin Xia; Liping Lin; Hao Tang; George Osei-Adjei; Shungao Xu; Yiquan Zhang; Xinxiang Huang (Current Microbiology, 2018)

Cross-shelf transport induced by coastal trapped waves along the coast of East China Sea - Lin Jiang; Changming Dong; Liping Yin (Journal of Oceanology and Limnology, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

Adsorption-Desorption Characteristics of Nonylphenol on Two Different Origins of Black Carbon - Guanghuan Cheng; Mingyang Sun; Xinlei Ge; Yang Ou; Xinhua Xu; Qi Lin; Liping Lou (Water, Air, & Soil Pollution, 2017)

Responses of root exudation and nutrient cycling to grazing intensities and recovery practices in an alpine meadow: An implication for pasture management - Geng Sun; Xia Zhu-Barker; Dongming Chen; Lin Liu; Nannan Zhang; Changguang Shi; Liping He; Yanbao Lei (Plant and Soil, 2017)

Association of MMP-9 C-1562T polymorphism with risk of Henoch-Schönlein purpura nephritis in children of southeast China - Jinwen Xu; Liping Zhao; Hongxia Zhou; Tingting Ge; Lin Zhang (Genes & Genomics, 2017)

Paleohydrological processes revealed by n-alkane δD in lacustrine sediments of Lake Pumoyum Co, southern Tibetan Plateau, and their response to climate changes during the past 18.5 cal ka - Yong Wang; Liping Zhu; Junbo Wang; Jianting Ju; Ping Peng; Xiao Lin; Jianfang Hu; Mitsugu Nishimura (Journal of Paleolimnology, 2016)

Interleukin-35 (IL-35) inhibits proliferation and promotes apoptosis of fibroblast-like synoviocytes isolated from mice with collagen-induced arthritis - Yunxia Li; Suqin Wu; Yuxuan Li; Shenyi Jiang; Tiantian Lin; Liping Xia; Hui Shen; Jing Lu (Molecular Biology Reports, 2016)

Estimating crop chlorophyll content with hyperspectral vegetation indices and the hybrid inversion method - Liang Liang; Zhihao Qin; Shuhe Zhao; Liping Di; Chao Zhang; Meixia Deng; Hui Lin; Lianpeng Zhang; Lijuan Wang; Zhixiao Liu (International Journal of Remote Sensing, 2016)

Pediastrum sensu lato (Chlorophyceae) assemblages from surface sediments of lakes and ponds on the Tibetan Plateau - Falko Turner; Liping Zhu; Xinmiao Lü; Ping Peng; Qingfeng Ma; Junbo Wang; Juzhi Hou; Qiuqi Lin; Ruimin Yang; Peter Frenzel (Hydrobiologia, 2016)

Characteristic pollen source area and vertical pollen dispersal and deposition in a mixed coniferous and deciduous broad-leaved woodland in the Changbai mountains, northeast China - Shengrui Zhang; Qinghai Xu; Marie-José Gaillard; Xianyong Cao; Jianyong Li; Liyan Zhang; Yuecong Li; Fang Tian; Liping Zhou; Fengyou Lin; Xiaolan Yang (Vegetation History and Archaeobotany, 2016)

Synthesis and biological evaluation of novel platinum complexes of imidazolyl-containing bisphosphonates as potential anticancer agents - Ling Qiu; Gaochao Lv; Yang Cao; Liping Chen; Hui Yang; Shineng Luo; Meifen Zou; Jianguo Lin (JBIC Journal of Biological Inorganic Chemistry, 2015)

Combined effect between two functional polymorphisms of SLC6A12 gene is associated with temporal lobe epilepsy - JINGYUN LI; HUA LIN; FENGHE NIU; XILIN ZHU; NING SHEN; XIN WANG; LIPING LI; AIHUA LIU; XIAOPAN WU; WEI SUN; YUPING WANG; YING LIU (Journal of Genetics, 2015)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

The time course of NO involved in ABA pathway to improve drought tolerance in Oxytropis ochrocephala Bunge - Huihui Zhuang; Wei He; Xi Chen; Lin Wang; Liping Ji; Bin Guo; Yahui Wei (Acta Physiologiae Plantarum, 2015)

Protective effects of intestinal trefoil factor (ITF) on gastric mucosal epithelium through activation of extracellular signal-regulated kinase 1/2 (ERK1/2) - Jinfeng Lin; Zhaorui Sun; Wei Zhang; Hongmei Liu; Danbing Shao; Yi Ren; Yanfang Wen; Liping Cao; Joy Wolfram; Zhizhou Yang; Shinan Nie (Molecular and Cellular Biochemistry, 2015)

Greenhouse gas intensity of three main crops and implications for low-carbon agriculture in China - Wen Wang; Liping Guo; Yingchun Li; Man Su; Yuebin Lin; Christian de Perthuis; Xiaotang Ju; Erda Lin; Dominic Moran (Climatic Change, 2015)

The effects of shRNA-mediated gene silencing of transcription factor SNAI1 on the biological phenotypes of breast cancer cell line MCF-7 - Yan Lu; Lina Yu; Minlan Yang; Xiangshu Jin; Zhijing Liu; Xiaowei Zhang; Liping Wang; Dongjing Lin; Yuanyuan Liu; Min Wang; Chengshi Quan (Molecular and Cellular Biochemistry, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

Characterization of the Zhikong Scallop (Chlamys farreri) Mantle Transcriptome and Identification of Biomineralization-Related Genes - Mingjun Shi; Ya Lin; Guangrui Xu; Liping Xie; Xiaoli Hu; Zhenmin Bao; Rongqing Zhang (Marine Biotechnology, 2013)

A Gel Filtration-Based Method for the Purification of Infectious Rotavirus Particles for Environmental Research Applications - Kata Farkas; Liping Pang; Susan Lin; Wendy Williamson; Richard Easingwood; Rayleen Fredericks; Mohamed A. Jaffer; Arvind Varsani (Food and Environmental Virology, 2013)

Origin of the pre-tropical storm Debby (2006) African easterly wave-mesoscale convective system - Yuh-Lang Lin; Liping Liu; Guoqing Tang; James Spinks; Wilson Jones (Meteorology and Atmospheric Physics, 2013)

An efficient method of noroviruses recovery from oysters and clams - Deqing Zhou; Liping Ma; Feng Zhao; Lin Yao; Laijin Su; Xinguang Li (Journal of Ocean University of China, 2013)

In vitro selection of glyphosate-tolerant variants from long-term callus cultures of Zoysia matrella [L.] Merr - Shu Chen; Mingliang Chai; Yufang Jia; Zhongshan Gao; Li Zhang; Minxia Gu; Wendan Lin; Liping Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Improved synthesis of 2′-deoxyadenosine and 5-methyluridine by Escherichia coli using an auto-induction system - Juan Xiong; Wenquan Zhang; Jingtan Su; Junlong Shangguan; Yin Lin; Yang Yang; Rongqing Zhang; Liping Xie; Hongzhong Wang (World Journal of Microbiology and Biotechnology, 2012)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

A pilot study on an attenuated Chinese EIAV vaccine inducing broadly neutralizing antibodies - Qinglai Meng; Yuezhi Lin; Jian Ma; Yan Ma; Liping Zhao; Shenwei Li; Hua Liang; Jianhua Zhou; Rongxian Shen; Xiaoyan Zhang; Yiming Shao (Archives of Virology, 2011)

Unique evolution characteristics of the envelope protein of EIAVLN40, a virulent strain of equine infectious anemia virus - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Jianhua Zhou (Virus Genes, 2011)

Genomic comparison between attenuated Chinese equine infectious anemia virus vaccine strains and their parental virulent strains - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Xiangang Kong; Jianhua Zhou (Archives of Virology, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

A meta-analysis of alcohol intake and risk of bladder cancer - Qiqi Mao; Yiwei Lin; Xiangyi Zheng; Jie Qin; Kai Yang; Liping Xie (Cancer Causes & Control, 2010)

Genomic analysis of an effective lentiviral vaccine-attenuated equine infectious anemia virus vaccine EIAVFDDV13 - Xu Qi; Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Rongxian Shen; Fenglong Wang; Xiangang Kong; Zhiqiang Su; et al. (Virus Genes, 2010)

Composition, spatial distribution, and environmental significance of water ions in Pumayum Co catchment, southern Tibet - Liping Zhu; Jianting Ju; Yong Wang; Manping Xie; Junbo Wang; Ping Peng; Xiaolin Zhen; Xiao Lin (Journal of Geographical Sciences, 2010)

Investigation of bathymetry and water quality of Lake Nam Co, the largest lake on the central Tibetan Plateau, China - Junbo Wang; Liping Zhu; Gerhard Daut; Jianting Ju; Xiao Lin; Yong Wang; Xiaolin Zhen (Limnology, 2009)

In vivo evolution of the gp90 gene and consistently low plasma viral load during transient immune suppression demonstrate the safety of an attenuated equine infectious anemia virus (EIAV) vaccine - Jian Ma; Chenggang Jiang; Yuezhi Lin; Xuefeng Wang; Liping Zhao; Wenhua Xiang; Yiming Shao; Rongxian Shen; Xiangang Kong; Jianhua Zhou (Archives of Virology, 2009)

Antifungal substances produced by Penicillium oxalicum strain PY-1—potential antibiotics against plant pathogenic fungi - Liping Yang; Jiatao Xie; Daohong Jiang; Yanping Fu; Guoqing Li; Fangcan Lin (World Journal of Microbiology and Biotechnology, 2008)

Adaptation of agriculture to warming in Northeast China - Xiu Yang; Erda Lin; Shiming Ma; Hui Ju; Liping Guo; Wei Xiong; Yue Li; Yinlong Xu (Climatic Change, 2007)

A dinuclear monofunctional platinum(II) complex with an aromatic linker shows low reactivity towards glutathione but high DNA binding ability and antitumor activity - Damin Fan; Xiaoliang Yang; Xiaoyong Wang; Shouchun Zhang; Jiafei Mao; Jian Ding; Liping Lin; Zijian Guo (JBIC Journal of Biological Inorganic Chemistry, 2007)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

DNA binding properties of novel cytotoxic gold(III) complexes of terpyridine ligands: the impact of steric and electrostatic effects - Pengfei Shi; Qin Jiang; Yongmei Zhao; Yangmiao Zhang; Jun Lin; Liping Lin; Jian Ding; Zijian Guo (JBIC Journal of Biological Inorganic Chemistry, 2006)

A New Format of Single Chain Tri-specific Antibody with Diminished Molecular Size Efficiently Induces Ovarian Tumor Cell Killing - Jing Liu; Qi Zhao; Baofeng Zhao; Julong Cheng; Xiangbin Wang; Liping Song; Zhang Zhong; Qing Lin; Hualiang Huang (Biotechnology Letters, 2005)

Hydrolysis activities of the particle of agarose-Ce4+ complex for compounds containing phosphodiester or peptide bonds - Lina Yu; Dongfeng Wang; Lin Su; Yi Luo; Liping Sun; Changhu Xue (Journal of Ocean University of China, 2005)

Pilot-Scale Fermentation and Purification of the Recombinant Allophycocyanin Over-Expressed in Escherichia coli - Baosheng Ge; Zhihong Tang; Liping Lin; Yuhong Ren; Yu Yang; Song Qin (Biotechnology Letters, 2005)

Novel Cu(II)-quinoline carboxamide complexes: Structural characterization, cytotoxicity and reactivity towards 5′-GMP - Junyong Zhang; Xiaokang Ke; Chao Tu; Jun Lin; Jian Ding; Liping Lin; Hoong-Kun Fun; Xiaozeng You; Zijian Guo (BioMetals, 2003)